Low Power Circuit Design Using Advanced CMOS Technology - Zhang, Milin; Wang, Zhihua; Van der Spiegel, Jan; Maloberti, F. (Tutorials in circuits and systems., 2018)
Offers a summary of lectures from the first Advanced CMOS Technology Summer School (ACTS) 2017. The slides are selected from the handouts, while the text was edited according to the lecturers talk.